Aquinas on Predication and Future Contingents. A Reply to Costa - Gili, Luca (European Journal for Philosophy of Religion, 2020)
In his paper “Aquinas, Geach, and Existence”, D. Costa maintains that Aquinas’ solution to the puzzle of future contingent events entails that future contingent entities already exist (in God’s perspective). This is tantamount to state that Aquinas endorsed a form of eternalism, since he maintained that past, present and future timelessly exist in God’s sight. I object that Aquinas’ texts are also compatible with another reading. In any statement of the form “S will be P”, the verb “will be” simply states the truth of the predicative link between S and P, not the existence of either S or P. In other words, I take the verb “to be” occurring in sentences describing future events as having the meaning of the “esse ut verum” (“being as true”).